A covalent organic framework/graphene aerogel electrocatalyst for enhanced overall water splitting. Issue 45 (8th November 2022) - Wang, Zhiya; Li, Jingfeng; Liu, Shiyin; Shao, Gaofeng; Zhao, Xiaojia
Abstract : The in situ growth of covalent organic frameworks at the macroscale on graphene aerogel surfaces for enhanced electrochemical water splitting. Abstract : The rational design of covalent organic framework (COF) based hybrid materials is of paramount importance to address the fundamental challenges of COFs with respect to their poor electron mobilization and the limited number of accessible active sites. Herein, we propose a new strategy for the fabrication of covalently bonded COF grafted graphene aerogel hybrid materials for electrocatalytic application. An in situ step-growth polymerization approach was developed to achieve the hybridization of COFs along the surface of amino-functionalized graphene nanosheets. By taking advantage of the three-dimensional conductive networks and highly accessible active sites, the cobalt-incorporated COF/graphene hybrid aerogel shows high oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) performances with an overpotential of 300 and 275 mV at 10 mA cm −2, respectively, under alkaline conditions. When applied to an electrochemical water-splitting electrolyzer, it is able to produce hydrogen and oxygen at competitive rates of 1.14 and 0.58 μL s −1, respectively, under ambient conditions, demonstrating its potential for practical applications.